Early pregnancy hemoglobin is associated with the risk of gestational diabetes mellitus: a retrospective cohort study - Heng, Yaw Yong; Mohd Shariff, Zalilah; Mohd Yusof, Barakatun Nisak; Rejali, Zulida; Yee, Yvonne Siang Tee; Bindels, Jacques; van der Beek, Eline M. (Cambridge University Press, 2022)
This study aimed to determine the association between hemoglobin (Hb) concentration and Hb change, during early to mid-pregnancy with the risk of gestational diabetes mellitus (GDM). This was a clinic-based retrospective cohort study of 1951 healthy pregnant women (18–45 years old) with a singleton gestation attending antenatal care at government health clinics. Hb concentration at first prenatal visit and each trimester was extracted from the antenatal cards. Hb changes from first prenatal visit to first and second trimester as well as from second to third trimester were calculated. Multivariate logistic regression was used with adjustment for covariates. Women with GDM had significantly higher Hb concentrations (Hb 1) at first prenatal visit (< 12 weeks) compared with non-GDM women (11·91 g/dl v.11·74 g/dl). Hb 1 and Hb changes (Hb change 2) from first prenatal visit to the second trimester (23–27th weeks) were significantly associated with GDM risk, with an adjusted OR of 1·14 (95 % CI 1·01, 1·29) and 1·25 (95 % CI 1·05, 1·49), respectively. The significant associations between Hb 1 and Hb change 2 with the risk of GDM were found among non-Malays, overweight/obese and women aged 35 years and above. Women with higher Hb concentrations in early pregnancy were at higher risk of GDM, and such association was significant among women aged 35 years and above, non-Malays and overweight/obese. This raises a potential concern for elevated Fe status in early pregnancy as a risk factor of GDM among Fe-replete women.